Cannabidiol inhibits paclitaxel-induced neuropathic pain through 5-HT(1A) receptors without diminishing nervous system function or chemotherapy efficacy - Ward, Sara Jane (British Journal of Pharmacology, 2014)
BACKGROUND AND PURPOSE: Paclitaxel (PAC) is associated with chemotherapy-induced neuropathic pain (CIPN) that can lead to the cessation of treatment in cancer patients even in the absence of alternate therapies. We previously reported that chronic administration of the non-psychoactive cannabinoid cannabidiol (CBD) prevents PAC-induced mechanical and thermal sensitivity in mice. Hence, we sought to determine receptor mechanisms by which CBD inhibits CIPN and whether CBD negatively effects nervous system function or chemotherapy efficacy. EXPERIMENTAL APPROACH: The ability of acute CBD pretreatment to prevent PAC-induced mechanical sensitivity was assessed, as was the effect of CBD on place conditioning and on an operant-conditioned learning and memory task. The potential interaction of CBD and PAC on breast cancer cell viability was determined using the MTT assay. KEY RESULTS: PAC-induced mechanical sensitivity was prevented by administration of CBD (2.5 – 10 mg·kg(−1)) in female C57Bl/6 mice. This effect was reversed by co-administration of the 5-HT(1A) antagonist WAY 100635, but not the CB(1) antagonist SR141716 or the CB(2) antagonist SR144528. CBD produced no conditioned rewarding effects and did not affect conditioned learning and memory. Also, CBD + PAC combinations produce additive to synergistic inhibition of breast cancer cell viability. CONCLUSIONS AND IMPLICATIONS: Our data suggest that CBD is protective against PAC-induced neurotoxicity mediated in part by the 5-HT(1A) receptor system. Furthermore, CBD treatment was devoid of conditioned rewarding effects or cognitive impairment and did not attenuate PAC-induced inhibition of breast cancer cell viability. Hence, adjunct treatment with CBD during PAC chemotherapy may be safe and effective in the prevention or attenuation of CIPN.